EFEKTIFITAS PROGRAM PENYULUH AGAMA ISLAM DALAM MEWUJUDKAN KELUARGA SAKINAH DI DESA MARGA MUKTI - Pipi Yuniarti; Ahmad Khobir (Al-Idaroh: Media Pemikiran Manajemen Dakwah, 2023)
Every family dreams of having a sakinah family. However, not all families know the meaning and how to get a sakinah family. Especially in Dusun 1 Marga Mukti, there were still early-age marriages. Their parents thouhgt that marrying their children at an early age will reduce their burden and responsibility. Their parents did not think about the impact of early-age marriage. And also in this village, there were still existing domestic violence. Therefore, this village requires a religious counselor to develop the families in getting harmonious family. Based on observations were conducted by the researcher after coaching by an Islamic religious instructor in creating a sakinah family in Marga Mukti village, it can provide very good benefits so that they understand the importance of a Sakinah family and they have good attitude as taught by our prophet Muhammad SAW.